Procedimentos para avaliação da qualidade da carne bovina in natura na recepção em serviços de alimentação - Mesquita, Marizete Oliveira de (2014)
Reception of innocuous fresh meat is relevant to the production of safe food by food services. Thus, federal sanitary legislation has determined the evaluation and approval of raw material during reception. The objective of this study was to develop procedures for characterizing the quality of fresh meat during reception in food services. In the first phase, when revising safety criteria, it was verified that federal legislation and technical standards for food services were recently published and present a wide, general approach concerning raw material reception. It determined specifications of criteria for evaluation and selection of suppliers, verification of transport system, requirements for the reception area, and the inspection of raw materials through the analysis of packaging, labeling, and temperature. In the second phase, when investigating supply and procedures for meat purchase in 35 university restaurants of Federal Institutions of Higher Education on the five regions of Brazil, it was observed that bovine meat was more frequent purchased in the South and Midwest regions, and that in the North and Northeast poultry was more frequently used. Still, the supply of meat products exceeds that of pork and fish in this region. Purchase occurred mainly by bidding in restaurants administered under the system of selfmanagement, resulting in meat provision by different suppliers. A nutritionist worked as technical manager. The main safety criteria on supplier selection were the requirement of product registration in the Inspection Service and of company regulation by the Health Surveillance. Weaknesses were found relating to physical and functional structures, transport system of the raw material, and record and monitoring of temperature. Was demonstrated, in the second phase of research, that Southeast restaurants presented a higher adequacy percentage to hygienic and sanitary criteria in meat reception, followed by the South, Midwest, Northeast, and North. The third phase was a case study about sanitary quality of fresh bovine meat approved in reception by a university restaurant of a Southern Federal Institutions of Higher Education. A descriptive sensorial method was applied to evaluate the quality of fresh bovine meat at reception. Documental, microbiological, and physical-chemical analysis were made using samples of lean bovine meat. The samples were fresh, cooled, vacuum bagged and not matured, and provided by slaughterhouses registered in the Federal Inspection System. The sensory parameters selected by the team to characterize fresh bovine meat were the appearance (color, uniformity, brightness) and odor (characteristic of fresh meat, metallic, rancid and strange). The sensory criterion was defined by association between the scores given by evaluators and counts of aerobic mesophilic and psychrotrophic microorganisms, pH values, temperature, and instrumental color of meat samples. Documentary analysis demonstrated adequacy to Best Practices procedures in meat reception. In addition to a positive experience to improve the supplier selection, the transport system, and the meat quality in public bidding purchase by including security criteria on bid notices. It became evident, through analysis, that the microbiological, physical-chemical, and sensory quality of the bovine meat purchased from qualified suppliers did not meet the security parameters established by legislative organs. Correlations between variables indicated that all physical-chemical tests, as well as sensory parameters of characteristic and strange odor, confirmed the counts of Aerobic mesophilic and psychrotrophic microorganisms. Color of the meat was correlated with the mold and yeast count. Upon considerations drawn from the development of this research, in the fourth phase, it was possible to formulate procedure for safe acquisition of fresh meat by food services. Consists of documents related to evaluation and selection of meat products suppliers; transport system evaluation; self-evaluation for reception area in food services; food handlers and technical manager; raw material inspection procedures (fresh meat); raw material return; raw material inspection plan.